If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = lx + 5l + 2 Reorder the terms: 2 = 2 + 5l + lx Add '-2' to each side of the equation. 2 + -2 = 2 + 5l + -2 + lx Combine like terms: 2 + -2 = 0 0 = 2 + 5l + -2 + lx Reorder the terms: 0 = 2 + -2 + 5l + lx Combine like terms: 2 + -2 = 0 0 = 0 + 5l + lx 0 = 5l + lx Solving 0 = 5l + lx Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-5l' to each side of the equation. 0 + -5l = 5l + -5l + lx Remove the zero: -5l = 5l + -5l + lx Combine like terms: 5l + -5l = 0 -5l = 0 + lx -5l = lx Add '-1lx' to each side of the equation. -5l + -1lx = lx + -1lx Combine like terms: lx + -1lx = 0 -5l + -1lx = 0 Factor out the Greatest Common Factor (GCF), '-1l'. -1l(5 + x) = 0 Ignore the factor -1.Subproblem 1
Set the factor 'l' equal to zero and attempt to solve: Simplifying l = 0 Solving l = 0 Move all terms containing l to the left, all other terms to the right. Simplifying l = 0Subproblem 2
Set the factor '(5 + x)' equal to zero and attempt to solve: Simplifying 5 + x = 0 Solving 5 + x = 0 Move all terms containing l to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + x = 0 + -5 x = 0 + -5 Combine like terms: 0 + -5 = -5 x = -5 Add '-1x' to each side of the equation. x + -1x = -5 + -1x Combine like terms: x + -1x = 0 0 = -5 + -1x Simplifying 0 = -5 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
l = {0}
| 10n+12=72 | | m+3=11+3m | | -21+4m=-5 | | 6x-3x-10=11 | | -6+m=-22 | | 2(12)+31+12n+11=180 | | -1a+1135=4a+105 | | X-1/5=-2/35 | | 2m+31=7m-29 | | 4x=x^2-16x+64 | | 7=bover-12 | | b+5+8=-1+3b | | 7-2k=13 | | -12a+194=-5a+152 | | 2(2x+15)4x=180 | | 5x-2y=7x+8 | | 19=9-2z | | 10+2k=4 | | 5x+9=3*-6 | | x-5=-13+x+5+x | | 10x-6-7x=3-6x | | 3(x+14)=5x-12 | | 3(-p-4)=-6(2+2p)+2p | | 5x+5x+7x+7x+8x+8x=720 | | 2(1+4v)=8+7(v-1) | | x=2-9x+20 | | X^2+29x-132=0 | | 25X=350 | | -8a-18=-2(-5+2a) | | 5k+7=2(k-1) | | -4a-6(6a+1)=-8(3+5a) | | 4-7b=-3b |